On the Variants of Thermal Process in Developing Strong and Ductile Medium Mn Steel - Pan, Shuai; He, Binbin (Frontiers in Materials, 2020)
In this contribution, we investigate the influence of three heat treatments, including intercritical annealing (IA), quenching and partitioning (Q&P) and combination of IA and Q&P (IA-Q&P), on microstructure and mechanical properties of the medium Mn steel. The steel treated by IA process has largest volume fraction of austenite, which is responsible for the longest elongation and largest energy absoprtion with operation of both transformation-induced plasticity (TRIP) effect and twinning-induced plasticity (TWIP) effects. The medium Mn steel produced by IA-Q&P treatment has a mixture microstructure with retained austenite, ferrite and lath martensite. The existence of martensite in the IA-Q&P steel makes the higher yield strength than that of the IA steel. The better uniform elongation of the IA-Q&P steel than that of the Q&P steel is ascribed to the larger volume fraction of retained austenite and higher mechanical stability of austenite. The Q&P steel has highest yield stress due to its martensite matrix. It is expected that the tensile properties of medium Mn steel can be tuned by different thermal processes (IA, Q&P and IA-Q&P) to facilitate its broad automotive applications.